Advertisement

### Question

Which of these is correct?

**A**

$\text"log"(1 + 2 + 3)$ = $\text"log"(1 × 2 × 3)$.

**B**

$\text"log"_4(4)$ = 4.

**C**

$\text"log"_6(6)$ = 36.

**D**

$\text"log"_2(1)$ = 2.

**Soln.**

**Ans: a**

Speaking factually, log(m + n + p) = log(m × n × p) is possible only if m × n × p = m + n + p, hence the answer, because 1 × 2 × 3 = 1 + 2 + 3. Expressions of the form $\text"log"_m(n) = p$ are same as m^{p} = n. We can see that none of the other options makes it correct.